2013
DOI: 10.1016/j.surg.2013.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Operatively induced chronic reflux in rats: A suitable model for studying esophageal carcinogenesis?

Abstract: Despite pathophysiologic differences with humans, the rat model of esophagoduodenostomy reproduces accurately histologic and molecular lesions in the carcinogenetic sequence of BE and allowed us to identify novel, tumor-associated proteins that may be potential biomarkers and new therapeutic targets in EA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Gronnier et al . later confirmed these results . However, they also identified Brunner's glands within the columnar lined esophageal segment.…”
Section: In Vivo Modelsmentioning
confidence: 53%
See 4 more Smart Citations
“…Gronnier et al . later confirmed these results . However, they also identified Brunner's glands within the columnar lined esophageal segment.…”
Section: In Vivo Modelsmentioning
confidence: 53%
“…The results suggested that bile was the key injurious factor and that gastric secretions alone had little effect. Despite key anatomical and histological differences between the murine and human esophagus, such as the presence of a keratinized squamous epithelium within the esophagus, an SCJ located within the forestomach, and the absence of esophageal submucosal glands (ESMGs), this paper served to popularize the murine model and formed the basis from which several later surgical reflux models were generated …”
Section: In Vivo Modelsmentioning
confidence: 99%
See 3 more Smart Citations